Determinants of Low Birth Weight in Indonesia: A Systematic Literature Review for Holistic Intervention Strategies - Arisanti, Atika Zahria; Rifalman, Alfusyifa (Universitas An Nasher - Cirebon, 2025)
Background: Low birth weight (LBW) is a significant global health indicator that reflects the overall well-being of mothers and infants. Its prevalence remains high in developing countries, including Indonesia. LBW is influenced by multiple interrelated factors—biological, socioeconomic, behavioral, and access to health services—that require holistic understanding and targeted interventions. Purpose: This study aims to identify the dominant determinants of LBW in Indonesia through a holistic approach by analyzing various contributing factors, including maternal health, social conditions, behavioral patterns, and healthcare accessibility. Method: The research was conducted using a systematic literature review with a narrative synthesis approach. Data sources included both quantitative and qualitative studies published in Indonesian and English. The quality of the studies was assessed using the Critical Appraisal Skills Program (CASP). Selected literature was analyzed based on four categories: medical, socioeconomic, behavioral, and access to health services. Result: The findings revealed that several key factors consistently contributed to the increased risk of LBW. These included high-risk maternal age (<20 years or >35 years), poor maternal nutritional status (anemia, chronic energy deficiency, low upper arm circumference), pregnancy complications (e.g., hypertension and prematurity), poor sanitation, maternal smoking, and insufficient antenatal care. Social determinants such as low educational attainment and limited access to healthcare services further exacerbated the risk. The study concludes that a multidimensional intervention strategy is essential, focusing on improving maternal nutrition, expanding access to quality health services, enhancing health education, and empowering women in making health-related decisions. Such integrative efforts are crucial to reducing LBW incidence and achieving the Sustainable Development Goals (SDGs), particularly those related to maternal and child health in Indonesia.